Within Wars and Revolutions: Helena Antipoff activities in the Bolshevik Russia (1917-1924) - Natalia Masolikova; Marina Sorokina (Cadernos de História da Educação, 2023)
The article deals with the professional career of the Russian psychologist Helena Antipoff (1892-1974) in the Soviet Russia, between 1917 and 1924, after returning from her educational stay in Paris and Geneva, and before migrating to Brazil in 1929. During the brief Soviet period, Helena was a witness and an active participant in the grandiose and dramatic changes of the country. Her work, as well as the work of other Russian scientists who migrated to other countries during the years of war and social revolution, is now being extensively studied, and new knowledge reverse some established perceptions and stereotypes about the history of psychology in Russia. Antipoff start-up in the Russian psychological and educational communities was linked to the intensive scientific and social activities of the St. Petersburg school of scientists and psychologists at this period – Vladimir M. Bekhterev (1857-1927), Alexander F. Lazursky (1874-1917), Alexander P. Nechaev (1870-1948), Mikhail Y. Basov (1892-1931), Adrian S. Griboedov (1875-1948) and others. Helena`s professional self-realization in this six-year Russian period was developed in real hot spots of practical psychological problems of that time for the country (study of children in conditions of devastation, hunger and orphanhood; testing of enhancement/reduction of child intelligence in conditions of social cataclysm and war; comparison of intellectual abilities of children of different social groups and in different countries; social and psychological diagnostics and distribution of “street children” to different types of care and educational institutions).